Separation membrane composite and method for producing the separation membrane composite

The separation membrane composite, featuring a polycrystalline interlayer and a mesoporous separation membrane with surface-introduced functional groups, addresses the challenges of uneven thickness and defects in existing mesoporous silica film formation methods, achieving enhanced permeation rate and separation performance.

JP7657517B2Active Publication Date: 2025-04-07NGK CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023510221
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-31
Filing Date
2021-11-29
Publication Date
2025-04-07
Estimated Expiration
2041-11-29

AI Technical Summary

Technical Problem

Existing methods for forming mesoporous silica films on porous supports face challenges such as uneven thickness, defects, and difficulty in introducing functional groups uniformly, which affect the separation performance and permeation rate.

Method used

A separation membrane composite is developed, comprising a porous support with a polycrystalline interlayer and a mesoporous separation membrane. The interlayer has a smaller average pore diameter than the support, preventing precursor solution penetration, and functional groups are introduced only on the surface side of the separation membrane to enhance permeation rate.

Benefits of technology

This approach allows for the proper formation of a separation membrane with increased permeation rate and high separation performance, while minimizing defects and uneven thickness issues.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657517000002
    Figure 0007657517000002
  • Figure 0007657517000003
    Figure 0007657517000003
  • Figure 0007657517000004
    Figure 0007657517000004
Patent Text Reader

Abstract

This separation membrane composite body (1) is provided with: a porous supporting body (11); an intermediate membrane (12) which is a polycrystalline membrane that is provided on a surface of the supporting body (11), while having pores that are derived from the skeleton structure and have a smaller average pore diameter than the pores in the vicinity of the surface of the supporting body (11); and a separation membrane (13) which is an inorganic membrane that is provided on the intermediate membrane (12), while having a regular pore structure. With respect to the separation membrane (13), a functional group is introduced into pores in a surface layer (14) that is away from the intermediate membrane (12). With respect to this separation membrane composite body (1), the separation membrane (13) is appropriately formed on the porous supporting body (11); and the permeation rate of a specific substance is able to be increased in the separation membrane (13) into which the functional group has been introduced.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a separation membrane composite and a method for producing a separation membrane composite. [Reference to Related Applications] This application claims the benefit of priority from Japanese patent application JP2021-60419, filed on March 31, 2021, the entire disclosure of which is incorporated herein by reference. [Background technology]

[0002] In recent years, it has been proposed to separate carbon dioxide (CO2) and other gases using mesoporous materials such as mesoporous silica. The precursor solution that is the raw material for mesoporous materials generally uses an organic solvent such as ethanol or IPA, and therefore has high fluidity. Therefore, when forming a membrane of a mesoporous material on a porous support, the precursor solution permeates into the porous support, making membrane formation extremely difficult.

[0003] Therefore, Japanese Patent No. 4212581 (Reference 1) proposes a method of impregnating the pores of a porous support with liquid paraffin as a pretreatment for producing a mesoporous silica thin film. A precursor solution is applied by spin coating onto the porous support impregnated with liquid paraffin to form a gel thin film. The liquid paraffin and the surfactant in the gel thin film are then removed by baking to obtain a mesoporous silica film. After that, a basic functional group is introduced into the mesoporous silica film using a silane coupling agent having a basic functional group.

[0004] However, when forming a mesoporous silica film on a tubular or monolithic porous support, the spin coating method cannot be used due to the shape of the support. In addition, when a method of impregnating such a porous support with liquid paraffin is adopted, it is not easy to impregnate the entire porous support with liquid paraffin, and the thickness of the mesoporous silica film will vary greatly (unevenness). As a result, defects such as poor coating of the mesoporous silica film will occur. This problem can also occur when forming a separation membrane other than a mesoporous silica membrane.

[0005] In addition, in the mesoporous silica membrane described in Reference 1, the introduction of basic functional groups increases the separation performance of CO2, but it is believed that basic functional groups are introduced into almost all of the pores, which reduces the permeation rate of CO2. This problem also occurs when functional groups that adsorb substances other than CO2 are introduced. Summary of the Invention

[0006] The present invention is directed to a separation membrane composite, and aims to properly form a separation membrane on a porous support and to increase the permeation rate of a predetermined substance in a separation membrane into which functional groups have been introduced.

[0007] A separation membrane composite according to a preferred embodiment of the present invention comprises a porous support, an intermediate film which is a polycrystalline membrane provided on the surface of the support, has pores derived from a skeletal structure, and has an average pore size smaller than the pores in the vicinity of the surface of the support, and a separation membrane which is an inorganic membrane provided on the intermediate film and has a regular pore structure. The functional groups are present in a biased state toward the surface side of the separation membrane. There are.

[0008] According to the present invention, a separation membrane can be appropriately formed on a porous support, and the permeation rate of a predetermined substance can be increased in the separation membrane into which a functional group has been introduced.

[0009] Preferably, the intermediate membrane has an average pore diameter of 0.1 to 1.0 nm, the separation membrane has an average pore diameter of 0.5 to 10.0 nm, and the intermediate membrane has an average pore diameter smaller than the average pore diameter of the separation membrane.

[0010] Preferably, the intermediate film is a film made of zeolite or a metal organic framework.

[0011] Preferably, the separation membrane is a membrane made of a mesoporous material, a zeolite or a metal-organic framework.

[0012] Preferably, in an X-ray diffraction pattern obtained by irradiating the surface of the separation membrane with X-rays, a peak appears in the range of 2θ=1 to 4°.

[0013] Preferably, the intermediate membrane has a thickness of 5 μm or less, and the separation membrane has a thickness of 1 μm or less.

[0014] Preferably, the functional group is an amino group.

[0015] The present invention is also directed to a method for producing a separation membrane composite. A method for producing a separation membrane composite according to a preferred embodiment of the present invention includes the steps of: a) preparing a porous support; b) forming an intermediate film on the surface of the support, the intermediate film being a polycrystalline film having pores derived from a skeletal structure, the average pore size of the pores being smaller than the average pore size of the pores in the vicinity of the surface of the support; c) forming a separation membrane, which is an inorganic film having a regular pore structure, on the intermediate film; and d) introducing functional groups into the pores in the surface layer of the separation membrane, which is distant from the intermediate film, by supplying a predetermined solution to the separation membrane. The intermediate film is impermeable to the precursor solution used to form the separation membrane in the step c) and the predetermined solution used in the step d).

[0016] The above and other objects, features, aspects and advantages will become more apparent from the following detailed description of the invention which proceeds with reference to the accompanying drawings. [Brief description of the drawings]

[0017] [Figure 1] FIG. 2 is a cross-sectional view of a separation membrane composite. [Diagram 2] FIG. 2 is an enlarged cross-sectional view showing a part of the separation membrane composite. [Diagram 3] FIG. 2 is a diagram showing a flow of manufacturing a separation membrane composite. [Figure 4] FIG. [Diagram 5] FIG. 1 is a diagram showing the flow of separation of a mixed material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] FIG. 1 is a cross-sectional view of a separation membrane composite 1. FIG. 2 is a cross-sectional view showing an enlarged portion of the separation membrane composite 1. The separation membrane composite 1 includes a porous support 11 and a laminated membrane 10 provided on the support 11. In FIG. 1, the laminated membrane 10 is depicted with a thick line. The laminated membrane 10 includes an intermediate membrane 12 and a separation membrane 13. The intermediate membrane 12 is provided on the support 11, and the separation membrane 13 is provided on the intermediate membrane 12. In FIG. 2, the intermediate membrane 12 and the separation membrane 13 are depicted with parallel diagonal lines. Furthermore, in FIG. 2, the intermediate membrane 12 and the separation membrane 13 are depicted as being thicker than they actually are.

[0019] The support 11 is a porous member that is permeable to gas and liquid. In the example shown in FIG. 1, the support 11 is a monolithic support having a single continuous columnar body that is molded integrally and has a plurality of through holes 111 that extend in the longitudinal direction (i.e., the left-right direction in FIG. 1). In the example shown in FIG. 1, the support 11 is substantially cylindrical. The cross section perpendicular to the longitudinal direction of each through hole 111 (i.e., cell) is, for example, substantially circular. In FIG. 1, the diameter of the through hole 111 is drawn larger than the actual diameter, and the number of the through holes 111 is drawn smaller than the actual number. The laminated film 10 is formed on the inner circumferential surface of the through hole 111 and covers the inner circumferential surface of the through hole 111 over substantially the entire surface.

[0020] The length of the support 11 (i.e., the length in the left-right direction in FIG. 1) is, for example, 10 cm to 200 cm. The outer diameter of the support 11 is, for example, 0.5 cm to 30 cm. The distance between the central axes of adjacent through holes 111 is, for example, 0.3 mm to 10 mm. The surface roughness (Ra) of the support 11 is, for example, 0.1 μm to 5.0 μm, and preferably 0.2 μm to 2.0 μm. The shape of the support 11 may be, for example, a honeycomb shape, a flat plate shape, a tubular shape, a cylindrical shape, a columnar shape, or a polygonal column shape. When the shape of the support 11 is a tubular or cylindrical shape, the thickness of the support 11 is, for example, 0.1 mm to 10 mm.

[0021] The material of the support 11 can be various substances (for example, ceramics or metals) as long as they are chemically stable in the process of forming the laminated film 10 on the surface. In this embodiment, the support 11 is formed of a ceramic sintered body. Examples of ceramic sintered bodies selected as the material of the support 11 include alumina, silica, mullite, zirconia, titania, yttria, silicon nitride, and silicon carbide. In this embodiment, the support 11 includes at least one of alumina, silica, and mullite.

[0022] The support 11 may contain an inorganic binder, which may be at least one of titania, mullite, sinterable alumina, silica, glass frit, clay minerals, and sinterable cordierite.

[0023] The average pore diameter of the support 11 is, for example, 0.01 μm to 70 μm, and preferably 0.05 μm to 25 μm. The average pore diameter of the support 11 in the vicinity of the surface on which the laminated film 10 is formed is 0.01 μm to 1 μm, and preferably 0.05 μm to 0.5 μm. The average pore diameter can be measured, for example, by a mercury porosimeter, a perm porosimeter, or a nanoperm porosimeter. Regarding the distribution of pore diameters throughout the support 11, including the surface and the inside, D5 is, for example, 0.01 μm to 50 μm, D50 is, for example, 0.05 μm to 70 μm, and D95 ​​is, for example, 0.1 μm to 2000 μm. The porosity of the support 11 in the vicinity of the surface on which the laminated film 10 is formed is, for example, 20% to 60%.

[0024] The support 11 has a multilayer structure in which, for example, a plurality of layers having different average pore diameters are laminated in the thickness direction. The average pore diameter and sintered grain size in the surface layer including the surface on which the laminated film 10 is formed are smaller than the average pore diameter and sintered grain size in the layers other than the surface layer. The average pore diameter of the surface layer of the support 11 is, for example, 0.01 μm to 1 μm, and preferably 0.05 μm to 0.5 μm. When the support 11 has a multilayer structure, the materials for each layer can be those described above. The materials for the layers forming the multilayer structure may be the same or different.

[0025] As described above, the laminated film 10 includes the intermediate film 12 provided on the surface of the support 11, and the separation membrane 13 provided on the intermediate film 12. The intermediate film 12 is a polycrystalline film, and is a porous film having pores (micropores) derived from the skeletal structure of the crystal. The intermediate film 12 is, for example, a film made of zeolite or metal-organic framework (MOF). The film made of zeolite or MOF means at least a film of zeolite or MOF formed on the surface of the support 11, and does not include a film in which zeolite or MOF particles are simply dispersed in an organic film. The intermediate film 12 may be formed of a substance other than zeolite and MOF.

[0026] The thickness of the intermediate film 12 is, for example, 0.05 μm to 30 μm. The thickness of the intermediate film 12 is preferably 5 μm or less, more preferably 4 μm or less, and further preferably 3 μm or less. The thickness of the intermediate film 12 is preferably 0.1 μm or more, and more preferably 0.5 μm or more. The thickness of the intermediate film 12 can be measured, for example, by imaging a cross section perpendicular to the intermediate film 12 using a scanning electron microscope (SEM) or a field emission scanning electron microscope (FE-SEM) (the same applies to the thickness of the separation membrane 13 described below).

[0027] The average pore diameter of the intermediate membrane 12 is preferably 1.0 nm or less, more preferably 0.8 nm or less, and even more preferably 0.6 nm or less. The average pore diameter of the intermediate membrane 12 is preferably 0.1 nm or more, more preferably 0.2 nm or more, and even more preferably 0.3 nm or more. The average pore diameter of the intermediate membrane 12 is smaller than the average pore diameter of the support 11 in the vicinity of the surface on which the intermediate membrane 12 is formed. In the production of the separation membrane composite 1 described below, when the precursor solution for forming the separation membrane 13 does not permeate the intermediate membrane 12, the average pore diameter of the intermediate membrane 12 may be larger than 1.0 nm.

[0028] A preferred intermediate film 12 is a film made of zeolite. When the maximum number of rings in the zeolite is n, the average pore size is the arithmetic mean of the short diameter and the long diameter of the n-ring pores. An n-ring pore is a pore in which the number of oxygen atoms in a portion in which an oxygen atom is bonded to a T atom to form a ring structure is n. When a zeolite has multiple types of n-ring pores with the same n, the arithmetic mean of the short diameter and the long diameter of all types of n-ring pores is the average pore size of the zeolite. In this way, the average pore size of a zeolite membrane is uniquely determined by the skeletal structure of the zeolite, and is listed in the "Database of Zeolite Structures" [online] of the International Zeolite Society, the Internet, and the like.<URL:http: / / www.iza-structure.org / databases / > The values ​​can be obtained from the values ​​disclosed in the

[0029] The type of zeolite constituting the intermediate film 12 is not particularly limited, and may be, for example, AEI type, AEN type, AFN type, AFV type, AFX type, BEA type, CHA type, DDR type, ERI type, ETL type, FAU type (X type, Y type), GIS type, LEV type, LTA type, MEL type, MER type, MFI type, MOR type, PAU type, RHO type, SAT type, SOD type, SZR type, or other zeolite. The intermediate film 12 is, for example, a DDR type zeolite. In other words, the intermediate film 12 is a zeolite membrane composed of zeolite whose structure code is "DDR" as defined by the International Zeolite Society. In this case, the intrinsic pore size of the zeolite constituting the intermediate film 12 is 0.36 nm x 0.44 nm, and the average pore size is 0.40 nm.

[0030] When the intermediate film 12 is a zeolite film, the intermediate film 12 contains, for example, silicon (Si). The intermediate film 12 may contain, for example, any two or more of Si, aluminum (Al) and phosphorus (P). In this case, the zeolite constituting the intermediate film 12 may be a zeolite in which the atom (T atom) located at the center of the oxygen tetrahedron (TO4) constituting the zeolite is only Si or is composed of Si and Al, an AlPO type zeolite in which the T atom is composed of Al and P, a SAPO type zeolite in which the T atom is composed of Si, Al and P, a MAPSO type zeolite in which the T atom is composed of magnesium (Mg), Si, Al and P, or a ZnAPSO type zeolite in which the T atom is composed of zinc (Zn), Si, Al and P. Some of the T atoms may be substituted with other elements.

[0031] When the intermediate film 12 contains Si atoms and Al atoms, the Si / Al ratio in the intermediate film 12 is, for example, 1 or more and 100,000 or less. The Si / Al ratio is preferably 5 or more, more preferably 20 or more, and even more preferably 100 or more, and the higher the ratio, the better. The Si / Al ratio in the intermediate film 12 can be adjusted by adjusting the compounding ratio of the Si source and the Al source in the raw material solution described later. The intermediate film 12 may contain an alkali metal. The alkali metal is, for example, sodium (Na) or potassium (K).

[0032] Similarly, when the intermediate film 12 is a film made of MOF, the average pore size of the intermediate film 12 can be calculated from the crystal skeleton structure. The type of MOF constituting the intermediate film 12 and the elements constituting the MOF are not particularly limited.

[0033] The separation membrane 13 is an inorganic membrane having a regular pore structure. The regular pore structure typically refers to one having a uniform pore size, and preferably refers to one showing a pore size distribution in a narrow range of 0.5 to 10 nm (for example, 90% or more of the pores are in this range). The separation membrane 13 is, for example, a membrane made of a mesoporous material, zeolite, or MOF. The membrane made of a mesoporous material, zeolite, or MOF is at least one in which a mesoporous material, zeolite, or MOF is formed in a membrane shape on the intermediate film 12, and does not include one in which mesoporous material, zeolite, or MOF particles are simply dispersed in an organic film. The separation membrane 13 may be formed of a material other than a mesoporous material, zeolite, and MOF. The separation membrane 13 can be used as a membrane that separates a specific substance from a mixture containing multiple types of substances by utilizing a molecular sieve effect. Other substances are less likely to permeate the separation membrane 13 than the specific substance. In other words, the permeation rate of the other substances through the separation membrane 13 is lower than the permeation rate of the specific substance.

[0034] The thickness of the separation membrane 13 is, for example, smaller than the thickness of the intermediate membrane 12. The thickness of the separation membrane 13 may be equal to or greater than the thickness of the intermediate membrane 12. The thickness of the separation membrane 13 is preferably 1 μm or less, more preferably 0.5 μm or less, and even more preferably 0.3 μm or less. Making the separation membrane 13 thinner increases the permeation rate of the specific substance. The thickness of the separation membrane 13 is preferably 0.1 μm or more, and more preferably 0.2 μm or more. Making the separation membrane 13 thicker improves the separation performance. The surface roughness (Ra) of the separation membrane 13 is, for example, 1 μm or less, preferably 0.5 μm or less, and more preferably 0.3 μm or less.

[0035] The average pore diameter of the separation membrane 13 is preferably 10.0 nm or less, more preferably 8.0 nm or less, and even more preferably 5.0 nm or less. The average pore diameter of the separation membrane 13 is preferably 0.5 nm or more, more preferably 1.0 nm or more, and even more preferably 2.0 nm or more. The average pore diameter of the separation membrane 13 is, for example, larger than the average pore diameter of the intermediate membrane 12. The average pore diameter of the separation membrane 13 may be equal to or smaller than the average pore diameter of the intermediate membrane 12.

[0036] A preferred separation membrane 13 is an amorphous membrane made of an oxide such as mesoporous silica or mesoporous carbon. Mesoporous silica or mesoporous carbon is formed using micelles of a surfactant as a template, and therefore the average pore size is determined by the type of surfactant used. The average pore size is the arithmetic mean of the short diameter and long diameter of the pores. When the separation membrane 13 is a membrane made of mesoporous silica or mesoporous carbon, the average pore size of the pores is, for example, 0.5 nm to 10.0 nm. The average pore size of the separation membrane 13 can be measured by a transmission electron microscope (TEM).

[0037] When separation membrane 13 is mesoporous silica or mesoporous carbon, a peak resulting from the regular pore structure of separation membrane 13 appears within a diffraction angle range of 2θ=1 to 4° in an X-ray diffraction (XRD) pattern obtained by irradiating the surface of separation membrane 13 with X-rays. In other words, the appearance of a peak within a range of 2θ=1 to 4° in the X-ray diffraction pattern indicates that separation membrane 13 has a regular pore structure of a preferred size. In addition, when obtaining an X-ray diffraction pattern, for example, CuKα radiation is used as the radiation source of an X-ray diffractometer.

[0038] The separation membrane 13 may be one that does not show a peak in the range of 2θ=1 to 4° in the X-ray diffraction pattern. For example, when the separation membrane 13 is a membrane made of zeolite or MOF, the above peak typically does not appear in the X-ray diffraction pattern. The separation membrane 13 that is a zeolite membrane or MOF membrane is a polycrystalline membrane and has pores derived from the skeletal structure of the crystal. Such a separation membrane 13 also has a roughly uniform pore size and can be said to be a membrane having a regular pore structure.

[0039] In the surface layer 14 of the separation membrane 13, which is away from the intermediate membrane 12, the surface of the pores is modified with a functional group that adsorbs a predetermined substance (for example, CO2). That is, the surface layer 14 including the surface of the separation membrane 13 is a functional group-introduced layer 14 in which a functional group has been introduced into the pores. The functional group-introduced layer 14 can also be regarded as an organic-inorganic hybrid layer in which the separation membrane 13, which is an inorganic membrane, is composited with a functional group of an organic substance. The functional group introduced into the functional group-introduced layer 14 is, for example, an amino group. In FIG. 2, the functional group-introduced layer 14 in the separation membrane 13 is marked with parallel oblique lines that intersect with the parallel oblique lines of the separation membrane 13.

[0040] In the separation membrane 13, the functional group introduction layer 14 is provided only on the surface side of the separation membrane 13, and is not provided on the intermediate membrane 12 side. In other words, in the separation membrane 13, the functional group introduction layer 14 (functional group) exists in a biased state on the surface side. The reason why such a functional group introduction layer 14 is formed is not clear, but one of the reasons is thought to be that the solution for introducing the functional group used in the production of the separation membrane composite 1 described later cannot permeate the pores of the intermediate membrane 12. If functional groups are introduced into all the pores in the separation membrane, a substance adsorbed to the functional group permeates the separation membrane by repeatedly adsorbing and desorbing with the functional group, so that the permeation resistance of the substance increases and the permeation rate decreases. In contrast, in the separation membrane composite 1, the functional group introduction layer 14 is provided only on the surface side of the separation membrane 13, so that the permeation resistance of the substance decreases and the permeation rate increases.

[0041] The presence of the functional group-introduced layer 14 can be confirmed by, for example, D-SIMS (Dynamic-SIMS). Although C and H detect moisture and the like, for example, in the case of a silane coupling agent containing an amino group, the amount of the supported agent can be measured by measuring the N element.

[0042] In D-SIMS, the concentration of an element (hereinafter referred to as "specific element") that is contained in the functional group in the functional group introduction layer 14 and is not contained in the separation membrane 13 (excluding the functional group) and the intermediate membrane 12 is measured in the depth direction from the surface of the separation membrane 13. If the concentration of the specific element gradually decreases (gradients) from the surface of the separation membrane 13 toward the intermediate membrane 12 and becomes almost constant before reaching the interface with the intermediate membrane 12, it can be said that the functional group introduction layer 14 is provided only on the surface side of the separation membrane 13 and is not provided on the intermediate membrane 12 side of the separation membrane 13. The concentration of the specific element in the immediate vicinity of the surface of the separation membrane 13 may be ignored because it is affected by contamination. If the distance from the surface of the separation membrane 13 to the position where the concentration of the specific element becomes almost constant is defined as the thickness of the functional group introduction layer 14, the thickness of the functional group introduction layer 14 is preferably 0.7 times or less, more preferably 0.5 times or less, of the thickness of the separation membrane 13. For example, the thickness of the functional group introduced layer 14 is 0.1 times or more the thickness of the separation membrane 13 .

[0043] Next, an example of a flow of manufacturing the separation membrane composite 1 will be described with reference to Fig. 3. Below, an example will be described in which a zeolite membrane is formed as the intermediate membrane 12 and a mesoporous silica membrane is formed as the separation membrane 13, but when other types of membranes are formed as the intermediate membrane 12 and the separation membrane 13, the same process as in Fig. 3 is performed using a well-known method for forming the membrane.

[0044] In the production of the separation membrane composite 1, first, a porous support 11 is prepared (step S11). Also, seed crystals to be used in the production of a zeolite membrane are prepared. In an example of forming a DDR-type zeolite membrane as the intermediate membrane 12, a DDR-type zeolite powder is produced by hydrothermal synthesis, and the seed crystals are obtained from the zeolite powder. The zeolite powder may be used as the seed crystals as it is, or the seed crystals may be obtained by processing the powder by pulverization or the like.

[0045] Next, the support 11 is immersed in the dispersion liquid in which the seed crystals are dispersed, and the seed crystals are attached to the support 11. Alternatively, the dispersion liquid in which the seed crystals are dispersed is brought into contact with a portion of the support 11 on which the interlayer film 12 is to be formed, thereby attaching the seed crystals to the support 11. In this way, a seed crystal-attached support is produced. The seed crystals may be attached to the support 11 by other techniques.

[0046] The support 11 to which the seed crystals are attached is immersed in the raw material solution. The raw material solution is prepared by dissolving and dispersing, for example, a Si source and a structure-directing agent (hereinafter also referred to as "SDA") in a solvent. The Si source is, for example, colloidal silica, sodium silicate, fumed silica, alkoxide, etc. The SDA contained in the raw material solution is, for example, an organic substance. The SDA is, for example, 1-adamantanamine. The solvent is, for example, water. Then, the seed crystals are used as nuclei to grow DDR-type zeolite by hydrothermal synthesis, thereby forming a DDR-type zeolite membrane as an intermediate membrane 12 on the support 11. The temperature during the hydrothermal synthesis is, for example, 80 to 200°C. The hydrothermal synthesis time is, for example, 3 to 100 hours.

[0047] After the hydrothermal synthesis is completed, the support 11 and the intermediate film 12 are washed with pure water. The washed support 11 and the intermediate film 12 are dried at, for example, 80°C. After the support 11 and the intermediate film 12 are dried, the SDA in the intermediate film 12 is burned and removed by heat treatment in an oxidizing gas atmosphere. This penetrates the micropores in the intermediate film 12. Preferably, the SDA is almost completely removed. The heating temperature for removing the SDA is, for example, 300 to 700°C. The heating time is, for example, 5 to 200 hours. The oxidizing gas atmosphere is an atmosphere containing oxygen, for example, air.

[0048] By the above process, the intermediate film 12 having penetrating pores is obtained (step S12). The intermediate film 12, which is a zeolite membrane, is a polycrystalline membrane and has pores derived from the skeletal structure. The average pore size of the pores in the intermediate film 12 is smaller than the pores in the vicinity of the surface of the support 11. In the formation of the zeolite membrane, the process of attaching seed crystals to the support 11 may be omitted, in which case the zeolite membrane is formed directly on the support 11.

[0049] Next, a precursor solution for forming the separation membrane 13 is prepared. The precursor solution is prepared by dissolving, for example, a silica source, a surfactant, an acid catalyst, and the like in a solvent. The silica source is, for example, tetraethyl triethoxysilane (TEOS), tetramethyl orthosilicate (TMOS), and the like. The surfactant may be, for example, a bromide or chloride such as cetyl trimethyl ammonium bromide (CTAB) or cetyl trimethyl ammonium chloride, but the present invention is not limited thereto. The acid catalyst is a pH adjuster, for example, hydrochloric acid, nitric acid, sulfuric acid, and the like. An alkali may be used as the pH adjuster. The solvent is, for example, an organic solvent such as ethanol or isopropyl alcohol (IPA). The blending ratio of each component in the precursor solution is appropriately set according to the type of mesoporous silica membrane to be formed, and the like.

[0050] The precursor solution is supplied onto the intermediate film 12 of the support 11. At this time, since the intermediate film 12 is impermeable to the precursor solution, the precursor solution does not pass through the pores of the intermediate film 12 and adheres to the surface of the intermediate film 12. That is, a film of the precursor solution is formed on the surface of the intermediate film 12. Excess precursor solution on the intermediate film 12 is preferably removed by, for example, air blowing. The solvent in the precursor solution is also removed by air blowing. Thereafter, the support 11 is heat-treated under an oxidizing gas atmosphere, whereby the surfactant in the film on the intermediate film 12 is burned and removed. As a result, a mesoporous silica film is formed as a separation film 13 on the intermediate film 12 (step S13). The separation film 13 has a regular pore structure. The heating temperature in removing the surfactant is, for example, 300 to 600° C. The heating time is, for example, 1 to 100 hours. The oxidizing gas atmosphere is an atmosphere containing oxygen, for example, air.

[0051] Here, if a separation membrane is formed on a support 11 on which an intermediate film 12 has not been formed, that is, if a precursor solution is directly supplied to the support 11, the precursor solution will seep into (permeate through) the pores of the support 11. As a result, a coating defect occurs in which a mesoporous silica film (separation membrane) is not partially formed on the surface of the support 11 on which the separation membrane is to be formed. In contrast, in the production of the separation membrane composite 1 in FIG. 3, the intermediate film 12 prevents or suppresses the seepage of the precursor solution into the pores of the support 11, so that a uniform separation membrane 13 can be formed without the occurrence of a coating defect due to the seepage of the precursor solution.

[0052] When the separation membrane 13 is formed, a solution for introducing a functional group is prepared. The solution for introducing a functional group is used for introducing a predetermined functional group, and is, for example, a solution in which a silane coupling agent is dissolved in a solvent. The solution for introducing a functional group is also called a hybridization solution. The functional group is one that adsorbs a predetermined substance (for example, CO2), and is, for example, a basic functional group having an amino group. Examples of the silane coupling agent include 3-aminopropyltriethoxysilane (APS), N1-(3-trimethoxysilylpropyl)diethylenetriamine, etc. Examples of substances having a basic functional group other than the silane coupling agent include amines. For example, ethylenediamine, 2-(2-aminoethylamino)ethanol, N-ethylethylenediamine, diethylenetriamine, isobutylamine, N-(2-aminoethyl)piperazine, etc., or polyethyleneimine. The solvent is, for example, an organic solvent such as toluene, methanol, ethanol, isopropanol, acetone, or THF (tetrahydrofuran).

[0053] The solution for introducing functional groups is supplied to the separation membrane 13. In this processing example, the support 11 on which the separation membrane 13 is formed is immersed in the solution for introducing functional groups at room temperature, and the solution is supplied to the separation membrane 13. The immersion time is, for example, 1 to 200 hours. At this time, the solution for introducing functional groups can permeate the pores of the separation membrane 13, but cannot permeate the pores of the intermediate membrane 12. That is, the separation membrane 13 is permeable to the solution for introducing functional groups, and the intermediate membrane 12 is impermeable to the solution for introducing functional groups. Therefore, the solution for introducing functional groups permeates into the pores of the separation membrane 13 only from the surface side of the separation membrane 13, and does not permeate into the pores of the separation membrane 13 from the intermediate membrane 12 side (support 11 side). After the immersion time has elapsed, the support 11 is taken out of the solution for introducing functional groups. As a result, functional groups are introduced into the pores of the surface layer 14 of the separation membrane 13, which is away from the intermediate membrane 12 (step S14). That is, an organic-inorganic hybridization is performed on the surface layer 14 of the separation membrane 13. Through the above processes, the production of the separation membrane composite 1 is completed.

[0054] As described above, in the separation membrane composite 1, the intermediate membrane 12 is provided on the surface of the porous support 11, and the separation membrane 13 having a regular pore structure is provided on the intermediate membrane 12. The intermediate membrane 12 is a polycrystalline membrane and has pores derived from the skeletal structure. In addition, the average pore size of the pores is smaller than that of the pores in the vicinity of the surface of the support 11. Therefore, the intermediate membrane 12 prevents or suppresses the precursor solution for forming the separation membrane from penetrating into the pores of the support 11. As a result, it is possible to appropriately form the separation membrane 13 on the support 11 (for example, a separation membrane 13 having a thickness of 1 μm or less, uniformly) while suppressing the occurrence of defects such as poor coating. In addition, in the separation membrane 13, which is an inorganic membrane, functional groups that adsorb a predetermined substance (for example, CO2) are introduced into the pores of the surface layer 14 away from the intermediate membrane 12. In the separation membrane 13, the range in which the functional groups are introduced is limited to the surface side, so that the permeation rate of the substance can be increased while realizing high separation performance.

[0055] When the functional group is an amino group, it is possible to increase the carbon dioxide permeation rate while realizing high separation performance. The functional group may be a group other than an amino group.

[0056] In a preferred separation membrane composite 1, the intermediate membrane 12 has an average pore size of 0.1 nm to 1.0 nm. This makes it possible to more reliably prevent or suppress the penetration of the precursor solution and the permeation of the solution for introducing functional groups into the intermediate membrane 12. Furthermore, by having an average pore size of 0.5 nm or more in the separation membrane 13, it is possible to realize a high permeation rate while modifying the inside of the pores with many functional groups. Furthermore, by having an average pore size of 10.0 nm or less in the separation membrane 13, it is possible to realize high separation performance while modifying the inside of the pores with functional groups.

[0057] Preferably, the thickness of the intermediate membrane 12 is 5 μm or less, and the thickness of the separation membrane 13 is 1 μm or less, which can more reliably increase the permeation rate of the predetermined substance.

[0058] Preferably, the intermediate film 12 is a film made of zeolite or a metal organic framework. This makes it easy to realize the intermediate film 12, which is a polycrystalline film and has pores derived from the skeletal structure. In addition, the penetration of the precursor solution and the permeation of the solution for introducing functional groups into the intermediate film 12 can be more reliably prevented or suppressed.

[0059] Preferably, separation membrane 13 is a membrane made of a mesoporous material, zeolite, or metal organic framework. This makes it possible to easily realize separation membrane 13 having a regular pore structure. In addition, it is preferable that a peak appears in the range of 2θ=1 to 4° in an X-ray diffraction pattern obtained by irradiating the surface of separation membrane 13 with X-rays. In this case, it can be said that a preferable separation membrane 13 having a regular pore structure has been realized.

[0060] The method for producing the separation membrane composite 1 includes a step of preparing a porous support 11 (step S11), a step of forming an intermediate film 12 on the surface of the support 11 (step S12), a step of forming a separation membrane 13 on the intermediate film 12 (step S13), and a step of introducing functional groups into pores of a surface layer 14 of the separation membrane 13 remote from the intermediate film 12 (step S14). The intermediate film 12 is impermeable to the precursor solution used to form the separation membrane 13 in step S13 and the solution for introducing functional groups used in step S14. This allows the separation membrane 13 to be appropriately formed on the porous support 11. Also, by introducing functional groups only to the surface side of the separation membrane 13, the permeation rate of a predetermined substance can be increased.

[0061] Next, examples of the separation membrane composite will be described. Table 1 shows the types and thicknesses of the intermediate membranes, the types and thicknesses of the separation membranes, the types of basic functional groups, and the measurement results of the CO2 permeation rates in Examples 1 to 10 and Comparative Example 1.

[0062] [Table 1]

[0063] <Example 1> (Preparation of intermediate film (DDR type zeolite film)) A monolithic alumina porous support was prepared, and seed crystals of DDR-type zeolite were attached to the inner surface of the through-holes. Next, a raw material solution was prepared by mixing colloidal silica, 1-adamantanamine, ethylenediamine, and water. The molar ratio of silica, 1-adamantanamine, ethylenediamine, and water was 1:1:0.25:100. After placing the alumina porous support with the DDR-type zeolite seed crystals attached in the fluororesin inner cylinder (internal volume 300 ml) of a stainless steel pressure-resistant container, the raw material solution was added and a heat treatment (hydrothermal synthesis: 130 ° C, 24 hours) was performed to form a high-silica DDR-type zeolite membrane on the inner surface of the through-holes. Next, the alumina support was washed and dried at 80 ° C for 12 hours or more. After that, the alumina support was heated to 450 ° C in an electric furnace and held for 50 hours to burn and remove the organic matter (SDA), and a DDR-type zeolite membrane was obtained as an intermediate film.

[0064] (Preparation of separation membrane (mesoporous silica membrane)) Tetraethyltriethoxysilane (hereinafter referred to as "TEOS") was prepared as the silica source, cetylmethylammonium bromide (hereinafter referred to as "CTAB") as the surfactant, hydrochloric acid as the acid catalyst, and ethanol (EtOH) as the solvent. TEOS and ethanol were mixed, and water adjusted to pH = 1.25 with hydrochloric acid was added to perform hydrolysis. CTAB was then added and dispersed in an ultrasonic cleaner. Further ethanol was added to make a precursor solution with a molar ratio of 1SiO2:0.1CTAB:5H2O:11.8EtOH.

[0065] In the monolithic porous support on which the zeolite membrane was formed, the precursor solution was poured into the inner periphery of the through-holes, and then the excess precursor solution was blown off with an air blower. The porous support was heated to 450°C in an electric furnace and held there for 50 hours to burn off the CTAB, yielding a separation membrane composite in which a mesoporous silica membrane, which is a separation membrane, was formed on the zeolite membrane.

[0066] (Organic-inorganic hybridization of separation membranes) A solution for introducing functional groups was prepared by mixing 3-aminopropyltriethoxysilane (APS), a silane coupling agent, with toluene. The separation membrane composite was immersed in the solution and kept at room temperature for 24 hours.

[0067] <Example 2> The procedure was the same as in Example 1, except that the silane coupling agent was changed to N1-(3-trimethoxysilylpropyl)diethylenetriamine.

[0068] <Example 3> The same as in Example 1 was used except that the basic functional group was changed to ethylenediamine.

[0069] <Example 4> The procedure was the same as in Example 1, except that the basic functional group was changed to 2-(2-aminoethylamino)ethanol.

[0070] <Example 5> The procedure was the same as in Example 1, except that the intermediate membrane was changed to an MFI type zeolite membrane.

[0071] (Preparation of intermediate membrane (MFI type zeolite membrane)) A monolithic alumina porous support was prepared, and MFI zeolite seed crystals were attached to the inner periphery of the through-holes. Next, a raw material solution was prepared by mixing silica, tetrapropylammonium bromide, and water. The molar ratio of silica, tetrapropylammonium bromide, and water was 1:0.25:100. After arranging the alumina porous support with the MFI zeolite seed crystals attached in the fluororesin inner cylinder (internal volume 300 ml) of a stainless steel pressure vessel, the raw material solution was added and a heat treatment (hydrothermal synthesis: 160 ° C, 24 hours) was performed to form a high-silica MFI zeolite membrane on the inner periphery of the through-holes. Next, the alumina support was washed and dried at 80 ° C for 12 hours or more. After that, the alumina support was heated to 450 ° C in an electric furnace and held for 50 hours to burn and remove the organic matter (SDA), and an MFI zeolite membrane was obtained as an intermediate film.

[0072] <Example 6> The same as in Example 5, except that the basic functional group was changed to 2-(2-aminoethylamino)ethanol.

[0073] <Example 7> The procedure was the same as in Example 1, except that the intermediate membrane was changed to a BEA type zeolite membrane.

[0074] (Preparation of intermediate membrane (BEA type zeolite membrane)) A monolithic alumina porous support was prepared, and seed crystals of BEA-type zeolite were attached to the inner periphery of the through-holes. Next, a raw material solution was prepared by mixing silica, tetraethylammonium hydroxide, hydrofluoric acid, and water. The molar ratio of silica, tetraethylammonium hydroxide, hydrofluoric acid, and water was 1:0.5:0.5:20. After placing the alumina porous support with the BEA-type zeolite seed crystals attached in the fluororesin inner cylinder (internal volume 300 ml) of a stainless steel pressure-resistant vessel, the raw material solution was poured in and a heat treatment (hydrothermal synthesis: 130°C, 96 hours) was performed to form a high-silica BEA-type zeolite membrane on the inner periphery of the through-holes. Next, the alumina support was washed and dried at 80°C for 12 hours or more. After that, the alumina support was heated to 450°C in an electric furnace and held for 50 hours to burn off the organic matter (SDA), and a BEA-type zeolite membrane was obtained as an intermediate film.

[0075] <Example 8> The procedure was the same as in Example 1, except that the intermediate film was changed to an FAU-type zeolite film, and the conditions for burning and removing CTAB during the preparation of the mesoporous silica film were changed to 300° C.×100 h.

[0076] (Preparation of intermediate membrane (FAU type zeolite membrane)) A monolithic alumina porous support was prepared, and seed crystals of FAU zeolite were attached to the inner periphery of the through-holes. Next, a raw material solution was prepared by mixing silica, sodium hydroxide, aluminum hydroxide, and water. The molar ratio of aluminum hydroxide, silica, sodium hydroxide, and water was 1:10:40:200. After placing the alumina porous support with the FAU zeolite seed crystals attached in the fluororesin inner cylinder (internal volume 300 ml) of a stainless steel pressure vessel, the raw material solution was added and a heat treatment (hydrothermal synthesis: 80 ° C, 10 hours) was performed to form a high-silica FAU zeolite membrane on the inner periphery of the through-holes. Then, the alumina support was washed and dried at 80 ° C for 12 hours or more.

[0077] <Example 9> The intermediate film (DDR type zeolite film) was prepared in the same manner as in Example 1, except that the basic functional group was changed to diethylenetriamine and the solvent was changed to water. The temperature for organic-inorganic hybridization was set to 80°C.

[0078] <Example 10> The procedure was the same as in Example 1, except that the intermediate film was changed to a MOF (UiO-66) film and the conditions for burning and removing CTAB during the preparation of the mesoporous silica film were changed to 300°C x 100 h.

[0079] (Preparation of intermediate film (MOF(UiO-66) film) ZrCl4, 1,4-benzenedicarboxylic acid, water, and acetic acid were added to DMF (dimethylformamide). The molar ratio of ZrCl4, 1,4-benzenedicarboxylic acid, water, acetic acid, and DMF was 1:1:1:100:200, and the mixture was left to stand at 120°C for 24 hours. After cooling, the mixture was washed with DMF to obtain the target product.

[0080] Water was added to the obtained UiO-66 to prepare a 0.05 wt% aqueous solution, and then the solution was ground in a ball mill for one day. A monolithic alumina porous support was prepared, and seed crystals of UiO-66 were attached to the inner surface of the through-holes. ZrCl4, 1,4-benzenedicarboxylic acid, water, and acetic acid were added to DMF, and the support was immersed in a solution containing ZrCl4, 1,4-benzenedicarboxylic acid, water, acetic acid, and DMF in a molar ratio of 1:1:1:100:600 at 130°C for 6 hours. After immersion, the support was washed successively with DMF and water.

[0081] <Comparative Example 1> The same procedure as in Example 1 was carried out except that the zeolite membrane as the intermediate membrane was not formed.

[0082] Next, the separation membrane composites of Examples 1 to 10 and Comparative Example 1 were subjected to various measurements and evaluations.

[0083] (interlayer and separator thickness measurement) The thicknesses of the zeolite membrane (intermediate membrane) and the mesoporous silica membrane (separation membrane) were measured by imaging the cross sections perpendicular to these membranes using a scanning electron microscope (SEM). In the separation membrane composites of Examples 1 to 10, a uniform mesoporous silica membrane with a thickness of 0.3 μm was formed. On the other hand, in the separation membrane composite of Comparative Example 1, the precursor solution seeped into the pores of the support, and no membrane was formed on the support surface, resulting in poor coverage of the mesoporous silica membrane.

[0084] (X-ray diffraction evaluation) For the X-ray diffraction (XRD) evaluation, an X-ray diffractometer (instrument name: MiniFlex600) manufactured by Rigaku Corporation was used. X-ray diffraction measurements were performed at a tube voltage of 40 kV, a tube current of 15 mA, a scanning speed of 0.5° / min, and a scanning step of 0.02°. The divergence slit was 1.25°, the scattering slit was 1.25°, the receiving slit was 0.3 mm, the incident Soller slit was 5.0°, and the receiving Soller slit was 5.0°. No monochromator was used, and 0.015 mm thick nickel foil was used as a CuKβ ray filter. After cutting the separation membrane composite at a plane including the central axis of any through hole, the surface of the mesoporous silica membrane was irradiated with X-rays.

[0085] In the X-ray diffraction patterns obtained from the separation membrane composites of Examples 1 to 10, a peak derived from the mesoporous silica membrane was observed near 2θ=3°, and peaks derived from the zeolite membrane or MOF membrane were observed from 5° onwards. In the X-ray diffraction pattern obtained from the separation membrane composite of Comparative Example 1, no diffraction peaks derived from the pores were observed in the range of 1 to 4°.

[0086] (D-SIMS evaluation) In the separation membrane composites of Examples 1 to 10, the surface of the mesoporous silica membrane was measured by D-SIMS, and the concentration of the nitrogen (N) element contained in the silane coupling agent gradually decreased (graded) from the surface of the mesoporous silica membrane toward the zeolite membrane, and became almost constant before reaching the interface with the zeolite membrane. In the separation membrane composites of Examples 1 to 10, since the mesoporous silica membrane is formed on the zeolite membrane or MOF membrane, it is presumed that the excessive penetration of the solution for introducing functional groups into the pores of the mesoporous silica membrane during hybridization is suppressed, and the concentration of the nitrogen element is high only in the surface layer of the mesoporous silica membrane. In the separation membrane composite of Comparative Example 1, the nitrogen element was detected non-uniformly throughout the support, and it is considered that the solution for introducing functional groups penetrated into the entire support.

[0087] (Membrane performance evaluation) Carbon dioxide (CO2) gas was introduced to the surface of the mesoporous silica membrane at 100°C and a pressure of 0.3 MPa, and the CO2 permeation rate was measured. In the separation membrane composites of Examples 1 to 10, a sufficiently high CO2 permeation rate was obtained compared to the separation membrane composite of Comparative Example 1.

[0088] Next, separation of a mixed substance using the separation membrane complex 1 will be described with reference to Figures 4 and 5. Figure 4 is a diagram showing a separation device 2. Figure 5 is a diagram showing a flow of separation of a mixed substance by the separation device 2.

[0089] In the separation device 2, a mixed substance containing multiple types of fluids (i.e., gases or liquids) is supplied to the separation membrane composite 1, and highly permeable substances in the mixed substance are separated from the mixed substance by permeating through the separation membrane composite 1. Separation in the separation device 2 may be performed, for example, for the purpose of extracting highly permeable substances from the mixed substance, or for the purpose of concentrating less permeable substances.

[0090] The mixed substance (i.e., mixed fluid) may be a mixed gas containing multiple types of gases, a mixed liquid containing multiple types of liquids, or a gas-liquid two-phase fluid containing both gas and liquid.

[0091] The mixture of substances may include one or more of the following: hydrogen (H2), helium (He), nitrogen (N2), oxygen (O2), water (H2O), water vapor (H2O), carbon monoxide (CO), carbon dioxide (CO2), nitrogen oxides, ammonia (NH3), sulfur oxides, hydrogen sulfide (H2S), sulfur fluoride, mercury (Hg), arsine (AsH3), hydrogen cyanide (HCN), carbonyl sulfide (COS), C1 to C8 hydrocarbons, organic acids, alcohols, mercaptans, esters, ethers, ketones, and aldehydes.

[0092] Nitrogen oxides are compounds of nitrogen and oxygen. Examples of the above-mentioned nitrogen oxides include nitric oxide (NO), nitrogen dioxide (NO2), nitrous oxide (also called dinitrogen monoxide) (N2O), dinitrogen trioxide (N2O3), dinitrogen tetroxide (N2O4), dinitrogen pentoxide (N2O5), etc. X The gas is called NOX.

[0093] Sulfur oxides are compounds of sulfur and oxygen. The above-mentioned sulfur oxides include, for example, sulfur dioxide (SO2), sulfur trioxide (SO3), and other SO X The gas is called SOXX.

[0094] Sulfur fluoride is a compound of fluorine and sulfur. The above-mentioned sulfur fluoride is, for example, disulfur difluoride (FSSF, S = SF2), sulfur difluoride (SF2), sulfur tetrafluoride (SF4), sulfur hexafluoride (SF6) or disulfur decafluoride (S2F 10 ) etc.

[0095] C1-C8 hydrocarbons are those with 1 to 8 carbon atoms. C3-C8 hydrocarbons may be straight-chain compounds, side-chain compounds, or cyclic compounds. C2-C8 hydrocarbons may be saturated hydrocarbons (i.e., those with no double or triple bonds in the molecule) or unsaturated hydrocarbons (i.e., those with double or triple bonds in the molecule). C1-C4 hydrocarbons are, for example, methane (CH4), ethane (C2H6), ethylene (C2H4), propane (C3H8), propylene (C3H6), normal butane (CH3(CH2)2CH3), isobutane (CH(CH3)3), 1-butene (CH2=CHCH2CH3), 2-butene (CH3CH=CHCH3), or isobutene (CH2=C(CH3)2).

[0096] The organic acid may be a carboxylic acid or a sulfonic acid. The carboxylic acid may be, for example, formic acid (CH2O2), acetic acid (C2H4O2), oxalic acid (C2H2O4), acrylic acid (C3H4O2), or benzoic acid (C6H5COOH). The sulfonic acid may be, for example, ethanesulfonic acid (C2H6O3S). The organic acid may be a chain compound or a cyclic compound.

[0097] The above-mentioned alcohols are, for example, methanol (CH3OH), ethanol (C2H5OH), isopropanol (2-propanol) (CH3CH(OH)CH3), ethylene glycol (CH2(OH)CH2(OH)) or butanol (C4H9OH).

[0098] Mercaptans are organic compounds that have hydrogenated sulfur (SH) at the end, and are also called thiols or thioalcohols. Examples of the mercaptans mentioned above include methyl mercaptan (CH3SH), ethyl mercaptan (C2H5SH), and 1-propanethiol (C3H7SH).

[0099] The esters mentioned above are, for example, formates or acetates.

[0100] The above-mentioned ethers are, for example, dimethyl ether ((CH3)2O), methyl ethyl ether (C2H5OCH3) or diethyl ether ((C2H5)2O).

[0101] The above-mentioned ketones are, for example, acetone ((CH3)2CO), methyl ethyl ketone (C2H5COCH3) or diethyl ketone ((C2H5)2CO).

[0102] The above-mentioned aldehydes are, for example, acetaldehyde (CH3CHO), propionaldehyde (C2H5CHO) or butanal (butyraldehyde) (C3H7CHO).

[0103] In the following description, it is assumed that the mixed substance separated by the separation device 2 is a mixed gas containing a plurality of types of gases.

[0104] The separation device 2 includes a separation membrane composite 1, a sealing unit 21, a housing 22, two sealing members 23, a supply unit 26, a first collection unit 27, and a second collection unit 28. The separation membrane composite 1, the sealing unit 21, and the sealing members 23 are housed in the housing 22. The supply unit 26, the first collection unit 27, and the second collection unit 28 are disposed outside the housing 22 and connected to the housing 22.

[0105] The sealing portion 21 is a member attached to both ends of the support 11 in the longitudinal direction (i.e., the left-right direction in FIG. 4) and covers and seals both longitudinal end faces and the outer peripheral surfaces near both end faces of the support 11. The sealing portion 21 prevents the inflow and outflow of gas from both end faces of the support 11. The sealing portion 21 is, for example, a plate-like member formed of glass or resin. The material and shape of the sealing portion 21 may be changed as appropriate. Note that the sealing portion 21 has a plurality of openings that overlap with the plurality of through holes 111 of the support 11, and therefore both longitudinal ends of each through hole 111 of the support 11 are not covered by the sealing portion 21. Therefore, gas and the like can flow in and out of the through holes 111 from both ends.

[0106] The shape of the housing 22 is not limited, but is, for example, a substantially cylindrical tubular member. The housing 22 is formed of, for example, stainless steel or carbon steel. The longitudinal direction of the housing 22 is substantially parallel to the longitudinal direction of the separation membrane composite 1. A supply port 221 is provided at one end of the longitudinal direction of the housing 22 (i.e., the left end in FIG. 4), and a first discharge port 222 is provided at the other end. A second discharge port 223 is provided on a side surface of the housing 22. A supply section 26 is connected to the supply port 221. A first collection section 27 is connected to the first discharge port 222. A second collection section 28 is connected to the second discharge port 223. The internal space of the housing 22 is a sealed space isolated from the space surrounding the housing 22.

[0107] The two seal members 23 are disposed around the entire circumference between the outer circumferential surface of the separation membrane composite 1 and the inner circumferential surface of the housing 22 near both ends of the separation membrane composite 1 in the longitudinal direction. Each seal member 23 is a substantially annular member made of a material that is gas impermeable. The seal member 23 is, for example, an O-ring made of a flexible resin. The seal member 23 is in close contact with the outer circumferential surface of the separation membrane composite 1 and the inner circumferential surface of the housing 22 around the entire circumference. In the example shown in FIG. 4, the seal member 23 is in close contact with the outer circumferential surface of the sealing portion 21, and indirectly in close contact with the outer circumferential surface of the separation membrane composite 1 via the sealing portion 21. The gap between the seal member 23 and the outer circumferential surface of the separation membrane composite 1 and the gap between the seal member 23 and the inner circumferential surface of the housing 22 are sealed, and gas is hardly or completely unable to pass through.

[0108] Supply unit 26 supplies the mixed gas to the internal space of housing 22 via supply port 221. Supply unit 26 is, for example, a blower or a pump that pressure-feeds the mixed gas toward housing 22. The blower or pump includes a pressure adjustment unit that adjusts the pressure of the mixed gas supplied to housing 22. First recovery unit 27 and second recovery unit 28 are, for example, storage containers that store the gas derived from housing 22, or blowers or pumps that transport the gas.

[0109] When the mixed gas is separated, the separation device 2 described above is prepared, and thus the separation membrane composite 1 is prepared (step S31). Next, the supply unit 26 supplies the mixed gas containing a plurality of types of gases having different permeabilities to the laminated membrane 10 (actually, adsorptivity to the functional group introduced to the separation membrane 13) to the internal space of the housing 22. For example, the main components of the mixed gas are CO2 and CH4. The mixed gas may contain gases other than CO2 and CH4. The pressure of the mixed gas supplied from the supply unit 26 to the internal space of the housing 22 (i.e., the introduction pressure) is, for example, 0.1 MPa to 20.0 MPa. The temperature at which the mixed gas is separated is, for example, 10°C to 150°C.

[0110] The mixed gas supplied from the supply unit 26 to the housing 22 is introduced into each through hole 111 of the support 11 from the left end of the separation membrane composite 1 in the figure, as shown by the arrow 251. A gas with high permeability in the mixed gas (e.g., CO2, hereinafter referred to as a "highly permeable substance") permeates the laminated membrane 10 provided on the inner circumferential surface of each through hole 111 and the support 11, and is discharged from the outer circumferential surface of the support 11. As a result, the highly permeable substance is separated from a gas with low permeability in the mixed gas (e.g., CH4, hereinafter referred to as a "lowly permeable substance") (step S32). The gas discharged from the outer circumferential surface of the support 11 (hereinafter referred to as a "permeating substance") is recovered by the second recovery unit 28 through the second discharge port 223, as shown by the arrow 253. The pressure of the gas recovered by the second recovery unit 28 through the second discharge port 223 (i.e., the permeation pressure) is, for example, about 1 atmosphere (0.101 MPa).

[0111] Furthermore, of the mixed gas, gases other than the gas that has permeated the laminated film 10 and the support 11 (hereinafter referred to as "non-permeating substances") pass through each through-hole 111 of the support 11 from left to right in the figure, and are recovered by the first recovery section 27 via the first discharge port 222, as shown by arrow 252. The pressure of the gas recovered by the first recovery section 27 via the first discharge port 222 is, for example, approximately the same as the introduction pressure. In addition to the above-mentioned low-permeability substances, the non-permeating substances may also include highly permeable substances that have not permeated the laminated film 10.

[0112] The above-mentioned separation membrane composite 1 and the method for producing the separation membrane composite 1 can be modified in various ways.

[0113] In the separation membrane composite 1, the intermediate membrane 12 may have an average pore size greater than 1.0 nm. The separation membrane 13 may have an average pore size less than 0.5 nm or greater than 10.0 nm. The intermediate membrane 12 may have a thickness greater than 5 μm, and the separation membrane 13 may have a thickness greater than 1 μm.

[0114] In the support 11 having a through hole, the laminated film 10 may be provided on either the inner peripheral surface or the outer peripheral surface, or may be provided on both the inner peripheral surface and the outer peripheral surface.

[0115] The separation membrane composite 1 may be produced by a method other than the above-mentioned production method.

[0116] In the separation device 2 and the separation method, substances other than the substances exemplified in the above description may be separated from the mixed substance.

[0117] The configurations in the above-described embodiment and each of the modified examples may be combined as appropriate as long as they are not mutually inconsistent.

[0118] Although the invention has been particularly illustrated and described, it is to be understood that the above description is illustrative and not restrictive, and therefore numerous modifications and variations are possible without departing from the scope of the invention. [Industrial Applicability]

[0119] The separation membrane composite of the present invention can be used, for example, as a carbon dioxide separation membrane, and further, can be used in various fields as a separation membrane for various substances other than carbon dioxide, an adsorption membrane for various substances, and the like. [Explanation of symbols]

[0120] 1 Separation membrane complex 11 Support 12 Interlayer 13 Separation membrane 14 Functional group introduction layer S11~S14, S31, S32 steps

Claims

1. A separation membrane composite, A porous support; an intermediate film which is a polycrystalline film provided on a surface of the support, the intermediate film having pores derived from a skeletal structure, the average pore diameter of the pores being smaller than that of the pores in the vicinity of the surface of the support; a separation membrane which is an inorganic membrane having a regular pore structure and is provided on the intermediate membrane; Equipped with A separation membrane composite, in which functional groups are introduced into pores in a surface layer of the separation membrane remote from the intermediate membrane, and the functional groups are present in a biased state toward the surface side of the separation membrane.

2. The separation membrane composite according to claim 1, The average pore size of the intermediate film is 0.1 to 1.0 nm; The separation membrane has an average pore size of 0.5 to 10.0 nm; A separation membrane composite, wherein the average pore size of the intermediate membrane is smaller than the average pore size of the separation membrane.

3. The separation membrane composite according to claim 1 or 2, The separation membrane composite, wherein the intermediate membrane is a membrane made of zeolite or a metal organic framework.

4. The separation membrane composite according to any one of claims 1 to 3, The separation membrane composite, wherein the separation membrane is a membrane made of a mesoporous material, a zeolite, or a metal-organic framework.

5. The separation membrane composite according to any one of claims 1 to 4, The separation membrane composite has an X-ray diffraction pattern obtained by irradiating the surface of the separation membrane with X-rays, in which a peak appears in the range of 2θ=1 to 4°.

6. The separation membrane composite according to any one of claims 1 to 5, A separation membrane composite, wherein the intermediate membrane has a thickness of 5 μm or less, and the separation membrane has a thickness of 1 μm or less.

7. The separation membrane composite according to any one of claims 1 to 6, The separation membrane composite, wherein the functional group is an amino group.

8. A method for producing a separation membrane composite, comprising the steps of: a) providing a porous support; b) forming an intermediate film on the surface of the support, the intermediate film being a polycrystalline film having pores derived from a skeletal structure, the average pore size of the pores being smaller than the average pore size of the pores in the vicinity of the surface of the support; c) forming a separation membrane, which is an inorganic membrane having a regular pore structure, on the intermediate membrane; d) supplying a predetermined solution to the separation membrane to introduce functional groups into pores in a surface layer of the separation membrane away from the intermediate membrane; Equipped with The method for producing a separation membrane composite, wherein the intermediate film is impermeable to the precursor solution used in forming the separation membrane in the step c) and the predetermined solution used in the step d).

Citation Information

Patent Citations

  • Mesoporous composite material and method for producing the same

    JP2007045691A

  • Carbon dioxide selective penetration complex type zeolite separation membrane, method for producing the same, and carbon dioxide selective penetration separation membrane element

    JP2012239939A

  • Mesoporous silica film on polymeric hollow fibers

    JP2013540588A

  • Separation membrane for treating acidic gas-containing gas and manufacturing method of separation membrane for treating acidic gas-containing gas

    JP2015174066A

  • Separation membrane structure

    WO2016084679A1